(untitled) (Bangladesh Journal of Psychiatry, 2019)
Obsessive compulsive disorder (OCD) is one of the most disabling psychiatric disorders. The purpose of the study was to find out the characteristics of patients with OCD attending a tertiary care psychiatry hospital in Bangladesh. This cross-sectional study was conducted in National Institute of Mental Health (NIMH), Dhaka from January 2021 to December 2021. Overall, 150 patients with OCD visited the outpatient and inpatient departments of the institution were selected conveniently. A pretested printed semi-structured questionnaire containing socio[1]demographic variables and variables related to OCD was applied for data collection. Data was collected by face to face interview with pen and paper method and data analysis was performed by statistical package for social sciences (SPSS) version 25. The results showed that the mean age of the respondents was 27.98 (±8.632) years. The male and female ratio was 1.3:1. More than half (51.3%) of the respondents were from urban background. Majority (33.3%) completed their graduation. Childhood (less than 18 year) onset of OCD was found among 42% of respondents, 86.7% respondents received treatment of OCD and among them 43.85% had treatment adherence. Almost three fourth (72%) of the them remained untreated for less than five years where others remained untreated for more than 5 years. Most of the respondents (88.7%) had no history of hospital admission and a considerable portion (39.3%) had family history of OCD. This study identified different factors related to OCD along with sociodemographic characteristics of the participants which might be used as baseline findings for future epidemiological studies. Bang J Psychiatry 2019; 33(2): 27-31